Minimal association between Th1-specific responses to COVID-19 vaccines and SARS-CoV-2 breakthrough infections in multiple sclerosis patients receiving disease-modifying therapies - Aiello, Alessandra; Navarra, Assunta; Haggiag, Shalom; Ruggieri, Serena; Cuzzi, Gilda; Vanini, Valentina; Salmi, Andrea; Notari, Stefania; Altera, Anna Maria Gerarda; Meschi, Silvia; Colavita, Francesca; Cimini, Eleonora; et al. (Frontiers in Immunology, 2025)
BackgroundThe COVID-19 pandemic highlighted challenges in managing patients with multiple sclerosis (PwMS), as disease-modifying therapies (DMTs) can interfere with immune responses to infections and vaccines.ObjectiveThis study investigates the spike-specific T-cell response after the third dose of mRNA COVID-19 vaccines in PwMS undergoing DMTs, evaluating different cytokines, beyond IFN-γ, and exploring their potential association with SARS-CoV-2 breakthrough infections (BI).MethodsWe prospectively enrolled 31 PwMS and 27 healthcare workers (HCWs). The spike-specific T-cell response was evaluated by measuring Th1 cytokines (IFN-γ, IL-2, TNF-α) and IP-10 using an easy-to-use whole-blood assay.ResultsMost PwMS mounted a Wuhan spike-specific T-cell response by releasing Th1 cytokines (IFN-γ, IL-2, TNF-α) and IP-10, albeit with significantly reduced Th1 cytokine levels compared to HCWs. Fingolimod-treated patients showed the weakest response with significantly reduced IFN-γ and IL-2 levels compared to HCWs (both p<0.0001), as well as to ocrelizumab (p=0.0018 and p=0.0002, respectively) and cladribine/IFN-β-treated patients (p=0.041 and p<0.0001, respectively). Moreover, a cell-mediated response was observed against the Delta spike variant, and all cytokines correlated with each other. BI occurred in 38.7% of PwMS, with predominantly mild COVID-19 cases. Male sex (IRR: 4.05, p=0.017) and primary progressive MS (IRR: 3.65, p=0.052) were associated with a higher BI incidence rate. Spike-specific T-cell response did not associate with a higher protection against BI.ConclusionsThis study provides an in-depth immunological characterization of the spike-specific T-cell response in PwMS under DMTs, evaluating immunological biomarkers whose relevance may extend beyond COVID-19 for studying immune responses to other infections and vaccinations.